2017
DOI: 10.1192/bjpo.bp.117.004861
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence and mental health of adolescents: South African Health and Well-being Study

Abstract: BackgroundMaterial and social environmental stressors affect mental health in adolescence. Protective factors such as social support from family and friends may help to buffer the effects of adversity.AimsThe association of violence exposure and emotional disorders was examined in Cape Town adolescents.MethodA total of 1034 Grade 8 high school students participated from seven government co-educational schools in Cape Town, South Africa. Exposure to violence in the past 12 months and post-traumatic stress disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…South African adolescents, and the South African population in general, report high rates of childhood abuse/trauma and alcohol/drug problems (Kaminer et al, 2013a, b; Parry et al, 2004; Stansfeld et al, 2018; Stein et al, 2008; Suliman et al, 2009). Furthermore, childhood abuse/trauma is positively associated with alcohol/drug problems in these samples (Morojele et al, 2016; Saban et al, 2014; Sommer et al, 2017) raising questions as to whether this relationship is mediated by coping motives.…”
Section: Introductionmentioning
confidence: 99%
“…South African adolescents, and the South African population in general, report high rates of childhood abuse/trauma and alcohol/drug problems (Kaminer et al, 2013a, b; Parry et al, 2004; Stansfeld et al, 2018; Stein et al, 2008; Suliman et al, 2009). Furthermore, childhood abuse/trauma is positively associated with alcohol/drug problems in these samples (Morojele et al, 2016; Saban et al, 2014; Sommer et al, 2017) raising questions as to whether this relationship is mediated by coping motives.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found that youth living in a post conflict setting have been exposed to some kind of violence in their community (Das-Munshi et al, 2017;Fausiah, Turnip, & Hauff, 2019;Kaminer, du Plessis, Hardy, & Benjamin, 2013;McAloney, McCrystal, Percy, & McCartan, 2009). The fact the community discussed political violence in an ease manner might be a sign of the increasing sense to tolerate violence.…”
Section: Resultsmentioning
confidence: 99%
“…These findings contrast with previous research indicating that social support fails to buffer the impact of violence exposure on adolescent mental health in high-violence contexts. [25,69] Similarly, community violence exposure was related to peer support of risky behaviour, but again only for boys, and significantly more strongly than for girls. It is possible that witnessing community violence exerts a stronger influence on boys' peer relationships than those of girls; boys who see violence may choose peers who approve of high-risk behaviour.…”
Section: Researchmentioning
confidence: 95%
“…RESEARCH studies have been conducted with schoolbased, [24][25][26] community-based [27,28] and/or con veni ence samples [20,29] in North America, Europe and SA, and these findings may not generalise to young people seeking mental health treatment. Importantly, teens receiving mental health services may be more accessible to interventions because they are already engaged in care.…”
mentioning
confidence: 99%